A NMR Experiment for Simultaneous Correlations of Valine and Leucine/Isoleucine Methyls with Carbonyl Chemical Shifts in Proteins - Tugarinov, Vitali (2013)
A methyl-detected ‘out-and-back’ NMR experiment for obtaining simultaneous correlations of methyl resonances of Valine and Isoleucine/Leucine residues with backbone carbonyl chemical shifts, SIM-HMCM(CGCBCA)CO, is described. The developed pulse-scheme serves the purpose of convenience in recording a single data set for all ILV methyl positions instead of acquiring two separate spectra selective for Valine or Leucine/Isoleucine residues. The SIM-HMCM(CGCBCA)CO experiment can be used for ILV methyl assignments in moderately sized protein systems (up to ~100 kDa) where the backbone chemical shifts of (13)C(α), (13)C(β) and (13)CO are known from prior NMR studies and where some losses in sensitivity can be tolerated for the sake of an overall reduction in NMR acquisition time.